The contractual imprevision. Brief comments regarding article 80 of the Cuban Civil Code - Carranza Álvarez, César (2008)
The present article analizes the institution of the contractual improvidence contained in the article 80 of the Cuban's Civil Code. It starts with a general view of the historic background, notion, main characters, and comparative legislation. Afterwards it analizes the content and the reaches of the mentioned norm, in some cases proposing some solutions to improve the legislation.